Capacitance-to-voltage converter design to measure small change in capacitance produced by human body movement - Arshad, Atika; Tasnim, Rumana; Alam, A.H.M Zahirul; Khan, Sheroz (Institute of Electrical and Electronics Engineers Inc., 2016)
The primary application of this work is to design and develop a reliable capacitance sensing system for measuring very small capacitive changes at low frequencies for human interface application. The sensing system is applicable in monitoring and characterizing human body movement. The interface circuit measures very small capacitive variation. A number of capacitive values have been set in the proposed system and the produced capacitance variations have been measured for verifying the possibility to characterize the presence/absence of human bodies. A variation in capacitance results in variation on the output voltage. Based on change in the voltage conclusion can be made regarding the presence/absence state of the human body. The sensing method is based on the fundamental principle of capacitance changes that is produced by the interaction of a human body with capacitive sensors. Different human body will exhibit different capacitance due to their height, weight and so on; giving each person distinctive identification. Primary simulation results show that the measurement of little capacitance variation using an interface circuit is precise and linear. The simulation results conclude that a very small capacitive variation can be detected using the developed capacitive sensing method. When a human body enters in the vicinity area right above the sensor, a variation in capacitance as well as output voltage can be observed.